Knowledge, Adoption and Effectiveness of Recommended Practices in Paddy and Cotton after Heavy Rains - J. Hemantha Kumar; Venkataramulu Manti; D. Vishnu Vardhan Reddy; CH Pragathi Kumari (Journal of Agricultural Extension Management, 2014)
A study was conducted to assess the Knowledge, Adoption and Effectiveness of recommended practices in paddy and cotton crops after heavy rains in Khammam district of Andhra Pradesh* during 2012-13. Frequency and percentages were used for statistical analysis. The study reveals that 100 per cent of the respondents have knowledge on draining out excess water from the field and majority of the farmers are adopting this practice after heavy rains. The reasons for not adopting other practices were due to lack of knowledge.